Unmanned Underwater Vehicles and the Normative Gaps of UNCLOS 1982: A Functional and Evolutionary Interpretation - Puspitawati, Dhiana; Susanto, Fransiska A.; Mohd Rusli, Mohd Hazmi; Wardana, Rangga Vandy (Universitas Negeri Gorontalo, 2026)
The rapid development of unmanned underwater vehicles (UUVs) presents a significant interpretative challenge to the United Nations Convention on the Law of the Sea 1982 (UNCLOS), a treaty drafted for an era of manned maritime navigation. While UNCLOS regulates ships and warships in detail, it remains silent on autonomous underwater systems. This article addresses the central legal question of whether, and under what conditions, UUVs may be classified as ships or warships under the existing UNCLOS framework. The study adopts a doctrinal legal methodology based on functional interpretation and evolutionary treaty interpretation, informed by the Vienna Convention on the Law of Treaties and relevant state practice. Rather than treating technological novelty as a basis for exclusion, the analysis examines whether the functions performed by UUVs—such as navigation, military operations, and marine scientific research—allow their regulation within established UNCLOS categories. The article argues that the legal status of UUVs cannot be determined abstractly, but depends on their operational function and the maritime zone in which they operate. Normatively, the article clarifies the limits of interpretative adaptation under UNCLOS and highlights the risks of fragmented, interest-driven state practice. It concludes that functional and evolutionary interpretation can reduce legal uncertainty, but must be complemented by bilateral and regional cooperative frameworks, including codes of conduct, to ensure regulatory coherence.